Application Of Self Nano Emulsifying Drug Delivery System For Clarithromycin (Journal of Pharmaceutical Negative Results, 2023)
The primary goal of this thesis is to develop a novel Self Nano-emulsifying drug delivery system to improve drug bioavailability in vitro and to increase clinical efficacy when administered orally.